Compositional and dimensional factors influencing pork belly firmness. (July 2017) - Soladoye, O.P.; Uttaro, B.; Zawadski, S.; Dugan, M.E.R.; Gariépy, C.; Aalhus, J.L.; Shand, P.; Juárez, M.
Abstract: We explored various dimensional and compositional factors that can influence the perception of pork belly firmness. Bellies from 198 pigs of three different genotypes, two sexes, two slaughter weights and three different diets were recovered and belly firmness was assessed using the belly-flop angle and a 5-point scale subjective measurement. Dimensional and compositional factors were recorded on intact and sheet-ribbed bellies. Subjective belly score was negatively correlated with belly-flop angle ( r  = − 0.89). Regression analysis accounted for 77 and 83% of the variability in subjective belly firmness and belly-flop angle measurement, respectively. Belly length, weight and width influenced both measures of belly firmness, but these effects were more important for the belly-flop angle. After correcting flop angle using belly length, the effect of belly weight disappeared and the effect of other traits was more like those observed for subjective scoring. Hence, undue effect of belly length should be corrected for if this set-up is to be implemented in commercial plants.